Intratumoral genomic heterogeneity in primary head and neck cancer and corresponding metastases detected by dual-FISH - Götte, Karl; Schäfer, Carsten; Riedel, Frank; Arens, Norbert; Hörmann, Karl (Oncology reports, 2004)
Intratumoral genomic heterogeneity, which can be defined as both intersample and intrasample heterogeneity, is still a poorly understood phenomenon in head and neck squamous cell carcinoma (HNSCC) with presumed implications on tumor behavior and even prognosis. We analyzed 89 tumor specimen from 37 HNSCC patients by fluorescence in situ hybridization (dual-FISH) using specific DNA probes binding to centromeric sites of 6 chromosomes to investigate intratumoral heterogeneity. A derivation from disomy in at least 1/6 chromosomes was detected in 88/89 (99%) specimen. In 33% of these samples, a change in ploidy could be suspected. Intrasample heterogeneity was detected in 68/89 (76%). Intrasample heterogeneity was more pronounced in primary tumors than in metastatic tumors. Analysis of the intersample heterogeneity revealed notable differences between the 6 chromosomes with the highest discordance detected for chromosome 3 (46%) and the lowest for chromosome 11 (27%). Following our results, it seems important to us to underline that intratumoral heterogeneity exists as intra- and sample heterogeneity in HNSCC. Altogether, trisomic cells were significantly more frequent in primary tumors than in metastases (p=0.01) while, in turn, monosomic cells were significantly more frequent in metastases (p=0.029). In individual cases the extent of discordance between corresponding samples made a common clonal precursor unlikely. In these cases, the synchronous development of a primary tumor and a carcinoma of unknown primary (‘CUP syndrome’), otherwise undetected, should be considered.